Question Number 166620 by mathlove last updated on 23/Feb/22 | ||
Answered by benhamimed last updated on 23/Feb/22 | ||
$${x}+\frac{\mathrm{1}}{{x}}\neq\sqrt{\mathrm{3}}\:\:\:\:\:\forall\:{x}\in\mathbb{R}^{\ast} \\ $$$$\left({x}+\frac{\mathrm{1}}{{x}}\right)'=\mathrm{1}−\frac{\mathrm{1}}{{x}^{\mathrm{2}} }=\frac{{x}^{\mathrm{2}} −\mathrm{1}}{{x}^{\mathrm{2}} } \\ $$$$\left.\left(\left.{x}+\frac{\mathrm{1}}{{x}}\right)\in\right]−\infty;−\mathrm{2}\right]\cup\left[\mathrm{2};+\infty\left[\right.\right. \\ $$ | ||
Answered by Rasheed.Sindhi last updated on 23/Feb/22 | ||
$${x}+\frac{\mathrm{1}}{{x}}=\sqrt{\mathrm{3}}\:\:;\:\:\:{x}^{\mathrm{18}} +{x}^{\mathrm{12}} +{x}^{\mathrm{6}} +\mathrm{1}=? \\ $$$$\bullet\left({x}+\frac{\mathrm{1}}{{x}}\right)^{\mathrm{3}} ={x}^{\mathrm{3}} +\frac{\mathrm{1}}{{x}^{\mathrm{3}} }+\mathrm{3}\left({x}+\frac{\mathrm{1}}{{x}}\right) \\ $$$${x}^{\mathrm{3}} +\frac{\mathrm{1}}{{x}^{\mathrm{3}} }=\left(\sqrt{\mathrm{3}}\:\right)^{\mathrm{3}} −\mathrm{3}\left(\sqrt{\mathrm{3}}\:\right)=\mathrm{3}^{\mathrm{3}/\mathrm{2}} −\mathrm{3}^{\mathrm{3}/\mathrm{2}} =\mathrm{0} \\ $$$$\bullet\left({x}^{\mathrm{3}} +\frac{\mathrm{1}}{{x}^{\mathrm{3}} }\right)^{\mathrm{3}} ={x}^{\mathrm{9}} +\frac{\mathrm{1}}{{x}^{\mathrm{9}} }+\mathrm{3}\left({x}^{\mathrm{3}} +\frac{\mathrm{1}}{{x}^{\mathrm{3}} }\right) \\ $$$${x}^{\mathrm{9}} +\frac{\mathrm{1}}{{x}^{\mathrm{9}} }=\left(\mathrm{0}\right)^{\mathrm{3}} −\mathrm{3}\left(\mathrm{0}\right)=\mathrm{0} \\ $$$$ \\ $$$$\:\bullet{x}^{\mathrm{18}} +{x}^{\mathrm{12}} +{x}^{\mathrm{6}} +\mathrm{1}={x}^{\mathrm{9}} \left(\frac{\:{x}^{\mathrm{18}} +{x}^{\mathrm{12}} +{x}^{\mathrm{6}} +\mathrm{1}}{{x}^{\mathrm{9}} }\right) \\ $$$$={x}^{\mathrm{9}} \left({x}^{\mathrm{9}} +\frac{\mathrm{1}}{{x}^{\mathrm{9}} }+{x}^{\mathrm{3}} +\frac{\mathrm{1}}{{x}^{\mathrm{3}} }\right)={x}^{\mathrm{9}} \left(\mathrm{0}+\mathrm{0}\right)=\mathrm{0} \\ $$ | ||